Coopercuc: valorization paths of local resources for living in harmony with the semiarid climate (Sustainability in Debate, 2016)
The history and evolution of the experience of the Cooperativa Agropecuária Familiar de Canudos, Uauá and Curaçá - Coopercuc, located in the state of Bahia, (Northeastern Brazil), exemplify the successful assertion of events and socio-cultural processes that can reverse the effects of some of the historical and sociopolitical factors associated with the main weaknesses of the Brazilian semiarid region. This article presents the context of this region and its critical issues. It seeks to show the sense of coexistence with the semiarid climate resulting from participation in the cooperative and in agroecological practices. It examines in an exploratory mode the history of Coopercuc, through field work, semi-structured interviews and qualitative data collection. Findings point to processes, agents and results that build a local development experience, which can be considered virtuous because of the sustainable and local social relations that foster integrated pathways of change and benefits.